The Biopotential of Bacterial Bioagents Isolated from Compost in Suppressing Botrytis cinerea and Sclerotinia sclerotiorum - Özden Salman; Raziye Koçak; Züleyha Endes Eğribaş (Turkish Journal of Agriculture: Food Science and Technology)
Recycling plant residues through various processes is essential for addressing waste issues in our country, because it contributes to the protection of the environment and ecosystems. Composting is one of the most important recycling methods for plant residues. Composts are not only natural, but they also enhance soil fertility and exhibit fungitoxic properties on the mycelial and spore germination of fungi. This study aimed to isolate bacterial bioagents from compost derived from various agricultural and household organic wastes, and to assess their antagonistic potential against important plant pathogens Botrytis cinerea and Sclerotinia sclerotiorum under in vitro conditions. A total of eight bacterial isolates were obtained, identified as belonging to Bacillus spp. Dual culture tests were used to evaluate the potential of these bacterial candidates to inhibit the mycelial growth of phytopathogenic fungi. In vitro trials revealed that six bacterial isolates exhibited varying degrees of antagonistic effects (23.3%- 63.3%) on the mycelial growth of B. cinerea. Among the tested bacteria, two isolates were effective against S. sclerotiorum, demonstrating antifungal activity ranging from 80% to 83.3%. The results indicate that composts provide a favorable environment for microorganisms with antagonistic potential, suggesting that these cultivation environments could play a significant role in the biological control of fungal pathogens in agriculture. In conclusion, this study contributes to the development of sustainable agricultural practices by ensuring a more efficient utilization of organic waste.